ANALISIS TINGKAT SUKU BUNGA DEPOSITO TERHADAP JUMLAH DANA DEPOSITO PADA PD. BPR. SARIMADU KANTOR KAS PASIR PENGARAIAN - Susanti; Nurhayati (AKPEM : Jurnal Akuntansi Keuangan dan Pemerintahan, 2022)
This study was conducted to analyze the effect of interest rates on the amount of deposit funds in PD. BPR. Sarimadu Pasir Pengaraian Cash Office, this study aims to see how much influence the deposit interest rate has on the term of deposit by using the report on the amount of funds in 2020.The analysis technique used is simple linear regression with hypothesis testing using T-statistics to test partial efficiency. This simple linear work uses the SPSS version 17.00 program tool.This research shows that the interest rate variable has a significant negative relationship with the amount of deposit funds.